A Phase 1, Randomized, Placebo‐Controlled Study to Evaluate the Safety, Tolerability, Pharmacokinetics, and Immunogenicity of Subcutaneous Tezepelumab in Healthy Japanese Men. Issue 7 (20th January 2020) - Sakamoto, Kei; Matsuki, Shunji; Irie, Shin; Uchida, Naoki; Hayashi, Nobuya; Horiuchi, Masato; Ren, Song
Abstract: Tezepelumab, a human immunoglobulin G2 monoclonal antibody against thymic stromal lymphopoietin, is currently under clinical development for the treatment of severe, uncontrolled asthma. This phase 1, randomized, placebo‐controlled, single‐ascending‐dose study assessed the safety, tolerability, pharmacokinetics, and immunogenicity of subcutaneous tezepelumab in healthy Japanese men. Participants were assigned to 1 of 3 tezepelumab dose cohorts (35, 105, or 280 mg; n = 8 per cohort) and randomized (6:2) to receive a single subcutaneous dose of tezepelumab or placebo, with a follow‐up period of 84 to 112 days. The overall incidences and severities of treatment‐emergent adverse events were similar across tezepelumab doses and between the tezepelumab and placebo groups. Tezepelumab was absorbed slowly, reaching a maximum serum concentration (mean, 5.2‐39.7 µg/mL) after 7 to 10 days. Area under the concentration‐time curve (mean, 207.2‐1612.0 µg · day /mL) increased in an approximate dose‐proportional manner. Tezepelumab had a long terminal serum half‐life (mean, 23.9‐26.3 days) and a small apparent distribution volume, suggesting limited distribution into peripheral tissues. No participants developed anti‐tezepelumab antibodies. Single‐dose, subcutaneous administration of tezepelumab 35 to 280 mg resulted in an acceptable safety profile with linear pharmacokinetics in healthy Japanese men. No clear differences in tezepelumab safety and pharmacokinetics between Japanese and non‐Japanese populations were identified.